A compressible and resilient chitosan / carbon black composite material and its preparation method and application
The preparation of chitosan/carbon black composite material was solved by ice template-assisted alkali replacement method, which solved the problem of poor mechanical properties of chitosan hydrogels, and achieved high toughness, compressible rebound and long-term salt resistance.
Patent Information
- Application Number
- CN202411157533.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-22
AI Technical Summary
In the prior art, chitosan hydrogels have poor mechanical properties, low toughness, easy to break, and are difficult to stabilize salt resistance in high concentration saline water for a long time.
Chitosan/carbon black composite material is prepared by ice template-assisted alkali replacement method to form a compressible resilient material with a hierarchical structure. During the freezing process, ice crystal growth makes chitosan molecular chains arranged locally in an orderly manner, alkali replacement enhances hydrogen bonding, and carbon black particles avoid excessive aggregation of molecular chains, forming a porous structure to improve mechanical properties.
The prepared chitosan/carbon black composite has good compression resilience under high stress, high toughness and can operate stably in high concentration saline for a long time, avoiding salt accumulation, and significantly improving salt resistance.
Smart Images

Figure CN118878936B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fiber composite materials, and in particular relates to a compressible and resilient chitosan / carbon black composite material and a preparation method and application thereof. Background Art
[0002] Chitosan is a marine biopolymer material with good biocompatibility, degradability and antibacterial properties. The linear molecular chain of chitosan contains abundant hydroxyl and amino functional groups, which can form fibers through intramolecular and intermolecular hydrogen bonding. High-strength and high-toughness chitosan fibers and fiber membranes can be prepared by wet spinning and electrospinning. The amino groups in chitosan molecules are easily protonated in acid. The protonated chitosan molecules can be dissolved in water. By adjusting the pH of the solution, the amino groups can be deprotonated in the process from acidic to alkaline. The deprotonated chitosan molecular chains establish intermolecular and intramolecular hydrogen bonds under alkaline conditions, thereby constructing a chitosan gel network. However, the distribution of chitosan molecular chains in the solution is usually disordered, which leads to the random construction of hydrogen bonds, so that the prepared chitosan gel has poor mechanical properties, is easy to break, and has low toughness. Even if a cross-linking agent such as glutaraldehyde is added, its brittleness cannot be avoided. Too much cross-linking agent will also cause the chitosan gel to be too hard and lose its flexibility.
[0003] In view of the above problems, the present invention proposes to prepare a hierarchical chitosan / carbon black composite material with both rigidity and flexibility, compressible resilience and a hierarchical structure by an alkali replacement method assisted by an ice template. The freezing-induced ice template can form a continuous porous sponge structure inside the material, and the chitosan molecular chains are locally arranged in an orderly manner with the help of ice crystal growth during the freezing process. The ice crystal template also promotes the concentration of the chitosan solution, thereby enhancing the hydrogen bonding effect within and between chitosan molecules. Alkali replacement deprotonates the protonated amino groups in the chitosan molecular chain, thereby further enhancing the hydrogen bonding effect of chitosan, effectively improving the structure and mechanical stability of the material. The addition of carbon black particles can effectively avoid excessive aggregation of chitosan molecular chains, thereby forming a hierarchical structure in which fibers overlap each other. The formed hierarchical structure has more abundant pores, which is more conducive to mechanical stress dissipation, and the addition of carbon black particles will not affect the crystallization behavior of chitosan molecules. The chitosan / carbon black composite material is used for evaporation and desalination of high-concentration salt water, which can achieve long-term stable salt resistance. Summary of the invention
[0004] In order to solve the problems of poor mechanical properties, low toughness and easy breakage of traditional chitosan hydrogels in the prior art, and to provide technical support for the preparation of chitosan composite materials with high mechanical strength, the present invention provides a compressible and resilient chitosan / carbon black composite material and its preparation method and application, and prepares a compressible and resilient chitosan / carbon black composite material with a hierarchical structure that has both rigidity and flexibility through an alkali replacement method assisted by an ice template. A three-dimensional porous chitosan / carbon black composite material is constructed by combining the hydrogen bonding within and between chitosan molecules with an ice template. The prepared chitosan / carbon black composite material has good compression and rebound effects under high stress and strain, and is used for evaporation and desalination of high-concentration brine. It can operate stably in high-concentration brine and has good salt resistance, which can solve the problem of salt accumulation during long-term operation of the evaporator.
[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a compressible and resilient chitosan / carbon black composite material, which is prepared by an ice template-assisted alkali replacement method. The material has a hierarchical pore structure, in which the large-size pore structure originates from the frozen ice template and has a pore size of >100 microns, and the small-size pore structure originates from the chitosan fiber network and has a pore size of <1 micron.
[0006] In a preferred embodiment of the present invention, the chitosan / carbon black composite material can maintain its original shape when compressed under low strain, and recover to its original shape after the compressive stress is removed under high strain. It can recover to its original shape after withstanding a maximum strain of 80%, and can undergo long-term compression cycles under a strain of 60%.
[0007] The present invention also protects a method for preparing a compressible and resilient chitosan / carbon black composite material, wherein a prepared chitosan and carbon black mixed acid solution is poured into a mold and then frozen in a refrigerator, and the frozen mixture is subjected to alkali substitution in a zero-degree ice water bath to obtain a chitosan / carbon black composite material. The positively charged chitosan molecular chains in the acidic solution promote the dispersion of the negatively charged carbon black particles, the ice template promotes the local concentration of the mixed solution, and the alkali substitution in the zero-degree ice water bath promotes the orderly hydrogen bond self-assembly process of the chitosan molecules.
[0008] In a preferred embodiment of the present invention, the preparation method comprises the following steps:
[0009] (1) preparing a dilute acid solution with a certain volume fraction, slowly adding a certain amount of chitosan powder into the dilute acid solution, and then continuously stirring until the chitosan powder is completely dissolved to form a transparent solution;
[0010] (2) adding a certain amount of carbon black powder to the solution obtained in step (1), stirring the mixture evenly and then ultrasonically crushing the mixture, casting the mixture of chitosan and carbon black into a mold, and freezing the mixture in a refrigerator;
[0011] (3) The chitosan / carbon black freeze-formed in step (2) is immersed in an alkaline solution in an ice-water mixed bath at zero degrees Celsius for solvent replacement; after the replacement reaction is completed, it is washed with deionized water until it is neutral to obtain a compressible and resilient chitosan / carbon black composite material.
[0012] In a preferred embodiment of the present invention, in step (1), the dilute acid solution is an aqueous solution of hydrochloric acid, glacial acetic acid or formic acid, etc., with a volume fraction of 1 to 5%, and the concentration of the obtained chitosan solution is 3 to 5wt%; preferably, the dilute acid solution is an aqueous solution of hydrochloric acid with a volume fraction of 5%, and the concentration of the obtained chitosan solution is 4wt%.
[0013] In a preferred embodiment of the present invention, in step (2), the amount of carbon black powder added is less than 0.4wt%, the ultrasonic crushing time is no more than 10 minutes, and the freezing time in the refrigerator is 24 to 48 hours; preferably, the amount of carbon black powder added is 0.3wt%, the ultrasonic crushing time is 10 minutes, and the freezing time in the refrigerator is 48 hours.
[0014] In a preferred embodiment of the present invention, in step (3), the alkaline solution is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia water, and sodium carbonate; the concentration of the alkaline solution is 1 to 10 wt %, and the soaking time is 2 to 72 hours; preferably, the alkaline solution is selected from sodium hydroxide, the concentration of the alkaline solution is 2.5 wt %, and the soaking time is 12 hours.
[0015] The present invention also protects a compressible and resilient chitosan / carbon black composite material evaporator. By adjusting the mold used in the freezing process, chitosan / carbon black composite materials of different shapes can be prepared, that is, a chitosan / carbon black composite material evaporator. The hierarchical structure inside the evaporator can promote the water-salt circulation in the process of desalination of high-concentration salt water; the evaporator has a high evaporation rate in high-concentration salt water and can work continuously and stably without salt accumulation.
[0016] The invention also protects the chitosan / carbon black composite material for evaporation and desalination of high-concentration salt water.
[0017] In a preferred embodiment of the present invention, the chitosan / carbon black composite material is placed above a heat insulation board, and water is supplied through a water-absorbing cotton core at the bottom. The heat insulation board is fixed on the top of an uncovered transparent container, and a certain volume of high-concentration salt water is contained in the container. The function of the heat insulation board is to prevent the evaporation of water other than the chitosan / carbon black composite material from causing a high evaporation rate. A xenon lamp (AM 1.5G) is used as a light source to irradiate downward, and a sunlight intensity is calibrated with an optical power meter. The mass change of the salt water in the container over time under sunlight irradiation is recorded by an electronic balance.
[0018] In a preferred embodiment of the present invention, the insulation board is a circular polystyrene foam board, the absorbent cotton core is a bamboo fiber cloth with an area the same as the cross-section of the bottom of the evaporator, the uncovered transparent container is a circular open glass cup, and the certain volume of high-concentration salt water is a 15wt% sodium chloride solution of half the volume of the container.
[0019] In summary, the compressible and resilient chitosan / carbon black composite material prepared by the present invention has a hierarchical pore structure, and has the advantages of high toughness and good compression and resilience. The prepared compressible and resilient chitosan / carbon black composite material is used for evaporation and desalination of high-concentration salt water, and the evaporator has the advantage of long-term salt resistance. Compared with the prior art, the present invention has the following advantages:
[0020] 1. The present invention uses a cryo-assisted alkali substitution technique to achieve the preparation of a three-dimensional chitosan / carbon black composite material with a hierarchical structure.
[0021] 2. The chitosan / carbon black composite material prepared by the present invention has good toughness, is compressible, and has excellent shape retention and compression rebound properties.
[0022] 3. The chitosan / carbon black composite material prepared by the present invention can be used for the evaporation and desalination of high-concentration salt water and can operate stably for a long time, with a high evaporation rate and no salt accumulation during long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The following is a further description with reference to the accompanying drawings.
[0024] Figure 1 This is a schematic diagram of the preparation of Example 1 of the present invention;
[0025] Figure 2 The scanning electron microscope images of CCH in Example 1 and CH in Example 2 of the present invention are shown;
[0026] Figure 3 The infrared spectra and XRD spectra of different samples in Example 1 and Example 2 of the present invention are shown;
[0027] Figure 4 The photographs of the changes of CCH under different stresses in Example 1 of the present invention;
[0028] Figure 5 The stress-strain curve, the cyclic compression curve at 60% strain and the shape recovery rate after compression cycle of CCH in Example 1 of the present invention;
[0029] Figure 6 The mass change curve and corresponding evaporation rate of the CCH evaporator in Example 1 of the present invention when the height is 4 cm and the 15 wt % sodium chloride solution is processed under one sunlight intensity for multiple cycles;
[0030] Figure 7 The photographs of the changes of CCH-G under different stresses in Example 4 of the present invention;
[0031] Figure 8 The evaporation rate variation curves of the 4 cm high evaporators of CCH in Example 1 and CCH-G in Example 4 of the present invention under different solar intensities. DETAILED DESCRIPTION
[0032] In order to make the technical content of the present invention more clearly understandable, embodiments of the present invention are described in detail below. However, the following embodiments are only used to explain the present invention, and the present invention is not limited to the following embodiments.
[0033] Example 1
[0034] A method for preparing a compressible and resilient chitosan / carbon black composite material comprises the following steps:
[0035] (1) preparing 40 mL of a 5% hydrochloric acid aqueous solution, slowly adding 4 wt % chitosan powder into the dilute hydrochloric acid, and then continuously stirring until the chitosan powder is completely dissolved to form a transparent solution;
[0036] (2) adding 0.3 wt % of carbon black powder to the chitosan solution of step (1), stirring evenly and then ultrasonically crushing for 10 minutes, casting the mixture of chitosan and carbon black into a cylindrical mold, and freezing in a refrigerator for 48 hours;
[0037] (3) The chitosan / carbon black freeze-formed in step (2) is taken out from the mold, immersed in 100 mL of a 2.5 wt% sodium hydroxide solution at zero degrees Celsius for a replacement reaction for 12 hours, and then washed with deionized water until neutral to obtain a compressible and resilient chitosan / carbon black composite material CCH.
[0038] In order to evaluate the shape maintenance ability of the chitosan / carbon black composite material CCH obtained in step (3), tests were carried out under low strain and high strain. Under low strain conditions, CCH can maintain its original shape without obvious deformation; under high strain, CCH recovers its shape after high strain compression. Figure 4 Photos of the changes of CCH under different stresses.
[0039] In order to evaluate the compression resilience of the chitosan / carbon black composite material CCH obtained in step (3), stress-strain test and compression cycle test were performed on CCH underwater. When the compression strain continued to increase from 20% to 80%, the stress-strain curve of CCH showed a closed-loop hysteresis curve, indicating that CCH deformed under pressure and fully recovered after the pressure was removed, and had good compression resilience. The stress-strain curve of the CCH composite material is clearly divided into two stages: when the strain is less than 60%, the stress increases nearly linearly, corresponding to the folding and unfolding of the porous network structure inside the chitosan / carbon black composite material CCH; when the strain is greater than 60%, the stress increases sharply, which is mainly due to the densification of the CCH structure after compression. CCH still shows strong compressive resistance and perfect shape recovery after 550 cycles at 60% strain. The shape recovery rate after the first cycle is 98.7%, and after the 550th cycle, the shape recovery rate of CCH can still be maintained at 93.76%. Figure 5 The stress-strain curve of CCH, the cyclic compression curve at 60% strain, and the shape recovery rate after compression cycle.
[0040] Example 2
[0041] A method for preparing a compressible and resilient chitosan gel material comprises the following steps:
[0042] (1) preparing 40 mL of a 5% hydrochloric acid aqueous solution, slowly adding 4 wt % chitosan powder into the dilute hydrochloric acid, and then continuously stirring until the chitosan powder is completely dissolved to form a transparent solution;
[0043] (2) casting the chitosan solution of step (1) into a circular mold, and freezing it in a refrigerator for 48 hours to obtain a frozen chitosan solution (CS frozen solution);
[0044] (3) The chitosan solution frozen in step (2) is taken out from the mold, immersed in 100 mL of 2.5 wt % sodium hydroxide solution at zero degrees Celsius for replacement reaction for 12 hours, and then washed with deionized water until neutral, to obtain a compressible and resilient chitosan gel material CH.
[0045] Scanning image by SEM ( Figure 2) It can be seen that CH presents an irregular porous structure, which is caused by the high viscosity of the chitosan solution and the uneven growth of ice crystals. The CH pore wall formed by ice crystal extrusion and alkali substitution presents a unique fibrous wrinkled structure. Due to the presence of carbon black, CCH has a smaller pore size and a richer porous network structure than CH. The pore structure of CCH can be divided into two levels: pores with a size of 100-200μm and pores with a size of <1μm. The two sizes of pores are interconnected by chitosan fibers to form a network structure. The emergence of CCH's richer porous network structure can be attributed to the introduction of carbon black particles, which breaks the hydrogen bond interaction of chitosan molecules and inhibits the excessive aggregation of chitosan molecular chains. The interconnected porous network structure not only allows water to be spontaneously transported upward to the top evaporation surface by capillary force, but also facilitates the water-salt circulation inside the CCH evaporator during the desalination process of high-concentration brine.
[0046] In order to evaluate the changes in the chemical composition and crystal structure of each sample in Examples 1 and 2, FTIR and XRD tests were performed ( Figure 3 ). In the raw chitosan powder, at 3405cm -1 The broad peak at 1600 cm is the stretching vibration of OH. -1 The peaks at 1138, 1050, and 1030 cm-1 are the in-plane bending vibrations of NH. -1 The peaks at 1513 cm-1 belong to the stretching vibrations of COC, secondary CO, and primary CO, respectively. -1 The peak at 1600 cm-1 in CH and CCH is mainly attributed to the symmetric deformation vibration of the protonated amino group, while in CH and CCH, the protonated amino group peak has disappeared due to the treatment with sodium hydroxide solution, corresponding to the deprotonation process in the base replacement. -1The NH bending vibration peak of the deprotonated amino group appeared at . In the frozen chitosan solution, CH and CCH, the peak intensity of OH and COC is weaker than that of the raw chitosan powder, and the position is shifted to the right, indicating that intramolecular and intermolecular hydrogen bonds are formed between the chitosan molecular chains. The XRD spectrum shows that the peak intensity of the frozen chitosan solution at 2θ=12° is stronger than that of the raw chitosan powder, indicating that the freezing process enhances the intermolecular hydrogen bonds of chitosan and improves the crystallinity of chitosan molecules. In the frozen chitosan solution, the peak position of the intramolecular hydrogen bond moves from 2θ=20° to 25.4° to the right, which is due to the increase in hydration caused by the protonation of the amino group. This peak will move back in CH and CCH due to the deprotonation process. However, compared with the raw chitosan powder, the peak position of the intramolecular hydrogen bond that moves back after deprotonation of CH and CCH is still shifted to the right by 0.6°, indicating that the base substitution leads to the rearrangement of the hydrogen bonds between the chitosan molecular chains, corresponding to the decrease in the lattice spacing. The peak at 2θ = 15° in CH and CCH corresponds to the anhydrous polycrystalline phase after base substitution. There is no significant difference in the peak position between CH and CCH, indicating that the addition of CB did not change the crystalline state of chitosan molecules. Figure 3 The infrared spectra and XRD spectra of different samples in Example 1 and Example 2 of the present invention are shown.
[0047] Example 3
[0048] In order to evaluate the evaporation and salt resistance performance of CCH in high-concentration brine in Example 1, a saline desalination cycle test was carried out. The specific test method is as follows:
[0049] The chitosan / carbon black composite material is placed on top of a heat-insulating circular polystyrene foam board, and water is supplied from the bottom through a bamboo fiber cloth with an area the same as the cross-section of the bottom of the evaporator. The polystyrene foam board is fixed on the top of a circular open glass cup, and a 15wt% sodium chloride solution of about one-half volume is filled in the container. The role of the polystyrene foam board is to prevent the evaporation of water other than the chitosan / carbon black composite material from causing a high evaporation rate. The simulated sunlight generated by a xenon lamp (AM 1.5G) is used as a light source to irradiate downward, and a sunlight intensity is calibrated with an optical power meter. The mass change of the salt water in the container over time under sunlight irradiation is recorded by an electronic balance. Figure 6 The mass change curve and corresponding evaporation rate of CCH in Example 1 in a continuous evaporation test of 9 hours in 15wt% brine.
[0050] Example 4
[0051] The chitosan / carbon black composite material is prepared by a room temperature chemical crosslinking method, which specifically comprises the following steps:
[0052] (1) preparing 40 mL of a 5% hydrochloric acid aqueous solution, slowly adding 4 wt % chitosan powder into the dilute hydrochloric acid, and then continuously stirring until the chitosan powder is completely dissolved to form a transparent solution;
[0053] (2) adding 0.3 wt % of carbon black powder to the chitosan solution of step (1), stirring evenly, and then ultrasonically crushing for 10 minutes, and then adding 0.6 wt % of glutaraldehyde in an ice water bath and stirring evenly;
[0054] (3) Casting the mixture obtained in step (2) into a mold, placing it at room temperature for a cross-linking reaction for 6 hours, and soaking it in clean water to wash away the residual reactants and allow it to fully swell to obtain a CCH-G hydrogel.
[0055] In order to evaluate the shape-maintaining ability of the chemically cross-linked chitosan / carbon black composite material CCH-G obtained in step (3), tests were performed under low strain and high strain. Under low strain conditions, CCH-G can maintain its original shape without obvious deformation; under high strain, CCH-G breaks due to mechanical brittleness. Figure 7 The photos are the changes of CCH-G under different stresses.
[0056] Example 5
[0057] In order to evaluate the water evaporation performance of CCH in Example 1 and CCH-G in Example 4 under high light intensity, a water evaporation test was performed. The specific test method is as follows:
[0058] The 4 cm high CCH and CCH-G evaporators were placed above a heat-insulating circular polystyrene foam board, and water was supplied from the bottom through a bamboo fiber cloth with the same area as the cross-section of the bottom of the evaporator. The polystyrene foam board was fixed on the top of a circular open glass cup, and the container was filled with about half the volume of water. The role of the polystyrene foam board is to prevent the evaporation of water other than the chitosan / carbon black composite material from causing a high evaporation rate. The simulated sunlight generated by a xenon lamp (AM 1.5G) was used as a light source to irradiate downward, and the light intensity of 1, 2, 3, and 4 sunlight was calibrated with an optical power meter. The mass of water in the container under sunlight irradiation was recorded by an electronic balance over time. By comparison, it can be seen that the evaporation rate of the CCH evaporator is higher than that of the CCH-G evaporator under the same sunlight intensity, and the gap gradually increases with the increase of sunlight intensity. Figure 8 The evaporation rate variation curves of the 4 cm high evaporators of CCH in Example 1 and CCH-G in Example 4 under different solar intensities.
[0059] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A compressible and resilient chitosan / carbon black composite material, characterized in that: The preparation method is an ice template-assisted alkali replacement method. The material has a hierarchical pore structure. The large-size pore structure comes from the frozen ice template, and its pore size is greater than 100 microns. The small-size pore structure comes from the chitosan fiber network, and its pore size is less than 1 micron. The preparation method includes the following steps: (1) preparing a dilute acid solution with a certain volume fraction, slowly adding a certain amount of chitosan powder into the dilute acid solution, and then continuously stirring until the chitosan powder is completely dissolved to form a transparent solution; (2) adding a certain amount of carbon black powder to the solution obtained in step (1), stirring the mixture evenly and then ultrasonically crushing the mixture, casting the mixture of chitosan and carbon black into a mold, and freezing the mixture in a refrigerator; (3) The chitosan / carbon black freeze-formed in step (2) is immersed in an alkaline solution in an ice-water mixed bath at zero degrees Celsius for solvent replacement; after the replacement reaction is completed, it is washed with deionized water until it is neutral to obtain a compressible and resilient chitosan / carbon black composite material.
2. The chitosan / carbon black composite material according to claim 1, characterized in that: The chitosan / carbon black composite material can maintain its original shape when compressed under low strain, and recover to its original shape after the compressive stress is removed under high strain. It can recover to its original shape after bearing a maximum strain of 80%, and can be subjected to long-term compression cycles under a strain of 60%.
3. The chitosan / carbon black composite material according to claim 1, characterized in that: In step (1), the dilute acid solution is an aqueous solution of hydrochloric acid, glacial acetic acid or formic acid, with a volume fraction of 1 to 5%, and the concentration of the obtained chitosan solution is 3 to 5 wt%.
4. The chitosan / carbon black composite material according to claim 3, characterized in that: The dilute acid solution is an aqueous solution of hydrochloric acid with a volume fraction of 5%, and the concentration of the obtained chitosan solution is 4wt%.
5. The chitosan / carbon black composite material according to claim 1, characterized in that: In step (2), the amount of carbon black powder added is less than 0.4 wt%, the ultrasonic crushing time is no more than 10 minutes, and the freezing time in the refrigerator is 24 to 48 hours.
6. The chitosan / carbon black composite material according to claim 5, characterized in that The added amount of carbon black powder is 0.3wt%, the ultrasonic crushing time is 10 minutes, and the refrigerator freezing time is 48 hours.
7. The chitosan / carbon black composite material according to claim 1, characterized in that: In step (3), the alkaline solution is selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia water, and sodium carbonate; the concentration of the alkaline solution is 1 to 10 wt %, and the soaking time is 2 to 72 hours.
8. The chitosan / carbon black composite material according to claim 7, characterized in that: The alkaline solution is selected from sodium hydroxide, the concentration of the alkaline solution is 2.5wt%, and the soaking time is 12 hours.
9. A compressible and resilient chitosan / carbon black composite evaporator, characterized in that: Chitosan / carbon black composite materials of different shapes are prepared by adjusting the mold used in the freezing process of the chitosan / carbon black composite material according to any one of claims 1 to 8, namely, a chitosan / carbon black composite material evaporator.
10. Use of the chitosan / carbon black composite material according to any one of claims 1 to 8 in evaporation and desalination of high-concentration salt water.
11. The use according to claim 10, characterized in that: A chitosan / carbon black composite material is placed above an insulation board, and water is supplied through an absorbent cotton core at the bottom. The insulation board is fixed on the top of an uncovered transparent container, and a certain volume of high-concentration brine is filled in the container. Simulated sunlight is used as a light source to irradiate downward, and a sunlight intensity is calibrated with an optical power meter. The mass change of the brine in the container over time under sunlight irradiation is recorded by an electronic balance.
Citation Information
Patent Citations
Chitosan-based gel material with double-layer-anisotropic structure as well as preparation method and application of chitosan-based gel material
CN112500586A
Shape memory chitosan hydrogel and preparation method thereof
CN112940287A